(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Mutualfunds are increasingly finding greater acceptance among investors, when itcomes to planning their finance. Like any other investment, mutual fundinvesting also has a lot of risk involved. Though the funds are managed byprofessionals and fund house have adequate risk management policies in place,so it is said that- Mutual fund is a mechanism for pooling the resources byissuing units to the investors and investing funds in securities in accordancewith the objectives as disclosed in offer document. Investment in securities isspread across a wide cross-section of industries and sectors and thus the riskis reduced. Diversification reduces the risk because all stocks may not move inthe same direction in the same proportion at the same time. Mutual fund issuesunits to the investors in accordance with quantum of money invested by them.Investors of mutual funds are known as unit holders.